Penyuluhan Berinternet dan Beribadah Pada Ibu Pengajian Perumahan Bandara Mas - Nia Ekawati (PUAN INDONESIA, 2020)
Over the years Islamic sites have sprung up. In addition to many new names, now the categories are also increasingly diverse. There is a portal of Islamic studies in general. There are also special for teens, families, or the public. Not only that. Now worship is increasingly free. Through the virtual universe can. From searching for Islamic references, the Koran and digital Hadiths, to participating in online study sessions, everything can be done. You can even download nasyid songs, Islamic wallpapers, to the call to prayer program for free. Now, we are referencing back a number of Islamic sites that are worthy of your visit. Some are old, but with a variety of new features. There is also something really new with a variety of information. Everything you can use to worship and strengthen faith. Koran recitals at the Mas Airport housing are an Islamic container that helps the residents of the Mas Airport housing to continue to carry out and implement Islamic law, such as recitation, lectures from informants. So that it can provide additional knowledge from the Islamic side